Strategi Pemasaran Digital Terintegrasi untuk Meningkatkan Visibilitas dan Performa Bisnis UMKM Kuliner - Vanessa Stephanie; Lady (LKP KARYA PRIMA KURSUS, 2026)
The Micro, Small, and Medium Enterprises (MSMEs) sector is a primary pillar of the Indonesian economy; however, many business owners still face challenges in adapting to digital transformation. Kwecap Aceng Tuapo, a traditional culinary business in Batam, faced challenges such as limited market reach and low digital visibility. This Community Service project aims to implement an integrated digital marketing strategy to enhance the partner's competitiveness. The method used is descriptive qualitative, with data collection techniques through field observations and in-depth interviews. The implementation stages include preparation, digital platform optimization, and impact evaluation. The results indicate that through the optimization of Google Business Profile, the development of branding content on Instagram, and the activation of GrabFood services, the partner successfully increased location visibility and transactional accessibility for consumers. Beyond expanding market reach, this program also succeeded in improving the partner's digital literacy, achieving managerial independence in platform management. In conclusion, the integration of various digital marketing channels has proven effective in strengthening business performance and the brand image of traditional culinary businesses in the digital era.